Antifungal amides from Piper hispidum and Piper tuberculatum - Navickiene, HMD; Alecio, A. C.; Kato, M. J.; Bolzani, Vanderlan da Silva [UNESP]; Young, MCM; Cavalheiro, Alberto José [UNESP]; Furlan, Maysa [UNESP] (Elsevier B.V., 2000)
Piper hispidum and Piper tuberculatum accumulate amides bearing isobutyl, pyrrolidine, dihydropyridone and piperidine moieties. The isolation and characterization of several representatives including two hitherto unreported amides were performed by chromatographic techniques and by analysis of spectroscopic data. The antifungal activity of each amide was determined by direct bioautography against Cladosporium sphaerospermum. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: Piper hispidum; Piper tuberculatum; Piperaceae; amides; antifungal activity